Working With School-Age Children, Part 2: Discipline - Millie Ferrer; Ingrid Rivera; Anne Fugate (EDIS, 2002)
This document is FCS2201, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: September 2002.